Assessment of yeast Saccharomyces cerevisiae component binding to Mycobacterium avium subspecies paratuberculosis using bovine epithelial cells. Issue 1 (December 2016) - Li, Ziwei; You, Qiumei; Ossa, Faisury; Mead, Philip; Quinton, Margaret; Karrow, Niel
Abstract Background Since yeastSaccharomyces cerevisiae and its components are being used for the prevention and treatment of enteric diseases in different species, they may also be useful for preventing Johne's disease, a chronic inflammatory bowel disease of ruminants caused byMycobacterium avium spp.paratuberculosis (MAP). This study aimed to identify potential yeast derivatives that may be used to help prevent MAP infection. The adherence of mCherry-labeled MAP to bovine mammary epithelial cell line (MAC-T cells) and bovine primary epithelial cells (BECs) co-cultured with yeast cell wall components (CWCs) from four different yeast strains (A, B, C and D) and two forms of dead yeast from strain A was investigated. Results The CWCs from all four yeast strains and the other two forms of dead yeast from strain A reduced MAP adhesion to MAC-T cells and BECs in a concentration-dependent manner after 6-h of exposure, with the dead yeast having the greatest effect. Conclusions The following in vitro binding studies suggest that dead yeast and its' CWCs may be useful for reducing risk of MAP infection.